1994
DOI: 10.1161/01.atv.14.6.874
|View full text |Cite
|
Sign up to set email alerts
|

Associations of allelic differences at the A-I/C-III/A-IV gene cluster with carotid artery intima-media thickness and plasma lipid transport in hypercholesterolemic-hypertriglyceridemic humans.

Abstract: Individuals with elevated levels of plasma cholesterol and triglyceride may be at higher risk for coronary artery disease than those with isolated elevations of either cholesterol or triglyceride. Sequence variation in the A-I/C-IH/A-IV gene cluster has been implicated in the etiology of some disorders associated with premature atherosclerosis and/or hypertriglyceridemias with or without elevations of cholesterol. This led to the hypothesis that allelic variation at this gene locus alters plasma lipid transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…In humans allelic variation in this complex has been associated with hyperlipoproteinaemia, 4 with hypertriglyceridaemia in obesity, 5 with the response of plasma lipid levels to diet, 6 and with atherosclerotic disease. 7 ApoA-IV is a component of triglyceride-rich lipoproteins, of HDL, and of the lipoprotein free plasma fraction. Both apoA-IV and apoA-I, the main protein constituent of HDL, participate in reverse cholesterol transport and confer protection against atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…In humans allelic variation in this complex has been associated with hyperlipoproteinaemia, 4 with hypertriglyceridaemia in obesity, 5 with the response of plasma lipid levels to diet, 6 and with atherosclerotic disease. 7 ApoA-IV is a component of triglyceride-rich lipoproteins, of HDL, and of the lipoprotein free plasma fraction. Both apoA-IV and apoA-I, the main protein constituent of HDL, participate in reverse cholesterol transport and confer protection against atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…An association between FCHL and an XmnI restriction fragment polymorphism in the 5Ј-flanking region of the apoA-I gene was reported, 12 and the finding was later confirmed by linkage (logarithm of the odds [lod] score, 6.86) without recombinants in 7 families. 13 Further evidence for an association between this gene cluster and FCHL has been provided by other groups, 14 -16 but the findings have also been challenged, [17][18][19][20] and the positive linkage result has not been confirmed. An explanation for this controversy may be provided by a recent study, 21 in which the contribution of the apoA-I/C-III/A-IV gene cluster is presented as an epistatic interaction between different haplotypes, a finding that may also partially explain the paradigm of the complex and varying phenotypes of FCHL.…”
mentioning
confidence: 99%
“…Key Words: genome scan Ⅲ lipids Ⅲ cholesterol Ⅲ triglyceride Ⅲ genetic linkage S erum lipoprotein-lipid levels are major risk factors for coronary heart disease, 1 and genes involved in lipoprotein metabolism have been implicated in coronary heart disease. [2][3][4] Discovery of the genetic determinants of quantitative variation in lipid levels could help to elucidate the genetics of coronary heart disease.Studies have indicated that lipid levels are significantly heritable. Point estimates of heritability for total cholesterol, HDL cholesterol (HDL-C), and plasma triglycerides (TGs) range from 42% to 65%, 45% to 83%, and 37% to 75%, respectively, with twin studies providing higher point estimates.…”
mentioning
confidence: 99%
“…Key Words: genome scan Ⅲ lipids Ⅲ cholesterol Ⅲ triglyceride Ⅲ genetic linkage S erum lipoprotein-lipid levels are major risk factors for coronary heart disease, 1 and genes involved in lipoprotein metabolism have been implicated in coronary heart disease. [2][3][4] Discovery of the genetic determinants of quantitative variation in lipid levels could help to elucidate the genetics of coronary heart disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation